Pengembangan Media Pembelajaran Maharah Kalam Menggunakan Aplikasi Plotagon Berbasis CTML di SD Muhammadiyah 18 Palembang - patma sari 2230204102; Kristina Imron; Irmansyah (WASIS : Jurnal Ilmiah Pendidikan, 2026)
This study aims to develop instructional media for maharah kalam using the Plotagon application based on the Cognitive Theory of Multimedia Learning (CTML) and to analyze its effectiveness in improving elementary school students’ Arabic speaking skills. The research employed a Research and Development (R&D) method using the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate) with a mixed-methods approach. The sample consisted of 24 Grade IV C students at SD Muhammadiyah 18 Palembang. Data were collected through interviews, observations, questionnaires, and tests. The results of expert validation showed that the developed media achieved a validity score of 88–90% from material experts and 87–91% from media experts, categorized as very valid. The effectiveness test indicated an improvement in students’ speaking skills, with the average pretest score of 62.5 increasing to 81.3 in the posttest. The N-Gain value reached 59.63%, which falls into the moderate (quite effective) category. Furthermore, the use of Plotagon-based media positively influenced students’ learning activities and motivation, as approximately 85% of students became more active and 80% showed increased confidence in practicing Arabic dialogues. In conclusion, the CTML-based Plotagon instructional media is feasible and effective in improving students’ Arabic speaking skills and creating a more engaging and communicative learning experience.